Development of early larviculture protocols for the melanurus wrasse Halichoeres melanurus - Groover, Elizabeth M.; Alo, Micah M.; Ramee, Shane W.; Lipscomb, Taylor N.; Degidio, Jon-Michael L.A.; DiMaggio, Matthew A. (Aquaculture, 2021)
The minority of marine ornamental species in the global trade today are produced through aquaculture. Culture of these species through their fragile larval stage remains a major impediment to commercialization and research into optimizing production protocols is needed. To date, only five ornamental wrasse species have been successfully cultured and no commercial production exists. The melanurus wrasse (Halichoeres melanurus) was chosen as a candidate for the development of culture methodologies due to popularity in the aquarium trade and short larval duration. A series of experiments were conducted which investigated embryo incubation temperatures, algal density and shading practices during larviculture, as well as prey type, density, and availability. Survival, growth, and feeding incidence were response variables of primary interest. An inverse relationship was found between water temperature and embryo incubation period and temperatures of 25 and 28 °C produced highest survival and smaller larvae at hatch. Evaluation of melanurus wrasse larvae prior to first feeding established that algal densities ≥50,000 cells mL−1 or artificial shading resulting in ~300 lx, enhanced growth and survival. Melanurus wrasse first feeding trials revealed that algal densities of 300,000 and 500,000 cells mL−1, provision of Parvocalanus crassirostris nauplii (<75 μm), and prey densities ≥5.0 items mL−1 resulted in elevated larval feeding success. Continued investigation into larviculture techniques influencing growth, survival, and feeding success should establish methodologies leading to commercial protocols for the melanurus wrasse and other marine ornamental species. •We evaluate effects of incubation temperature, algal density, and prey type and density on Melanurus wrasse larvae.•An inverse relationship was found between water temperature and embryo incubation period.•Algal densities of ≥300,000 cells mL−1 and P. crassirostris nauplii (≥5.0/mL−1) increased larval feeding success.